Hope and Despair in the One Night @ the Call Center by Chetan Bhagat: Exploring Hope and Despair in Chetan Bhagat's One Night @ the Call Center (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Chetan Bhagat is an Indian novelist, columnist and motivational speaker. His best famous five novels are in this way for which he is well-known Five Point Someone, The 3 Mistakes of My life, One Night the Call Center, 2 States and What Young India Wants. His language is very lucid and easy to understand. This paper focus upon the personal issues of hope and despair in Chetan Bhagat’s One night the call center. He is a typical author that lies in the mind of the common man. He is dealing with the harsh realities of life and problems faced by the young generation in his works. He holds a mirror to society and presents the reflection of the society of our own country. He selects subject which a reader can associate with socio scientific issues.